Caenorhabditis elegans as a powerful tool in natural product bioactivity research - Ha, Ngoc Minh; Tran, Son Hung; Shim, Yhong-Hee; Kang, Kyungsu (한국응용생명화학회, 2022)
In addition to synthetic and semisynthetic compounds, natural products have received much attention as prolific sources of lead compounds with therapeutic effects on various diseases. In the process of screening the bioactivities of potential candidates, an in vivo assay is very important for providing meaningful insight into the efficacy, adverse effects, and modes of action that are relevant to humans. Among the many experimental models, Caenorhabditis elegans is particularly efficient due to its advantages in morphology, behavior, and genetic aspects. This review summarizes some basic and useful techniques commonly used in screening the bioactivities of natural products. Recent studies of naturally occurring extracts as well as bioactive compounds in various areas, namely, anti-aging, anti-neurodegeneration, anti-obesity, anti-infection, and gut health, are reviewed as examples of the applicability of the C. elegans model. Technological developments that incorporate C. elegans in other fields, such as instrumental analysis and emerging methods, are also discussed in this paper.